Neuro‐COVID: Does severe COVID‐19 infection increase the risk for cognitive impairment?. (31st December 2021) - Hagman, Göran; Thunborg, Charlotta; Andersen, Pia; Levak, Nicholas; Aspö, Malin; Walles, Håkan; Jokhader, Elias; Kåhlin, Jessica; Nelson, David; Piehl, Fredrik; Tzortzakakis, Antonios; Zetterberg, Henrik; et al.
Abstract: Background: Neurocognitive manifestations of the coronavirus disease 2019 (COVID‐19) have been reported in the acute phase, especially in critically ill patients. The potential mechanisms underlying these symptoms are not fully understood but probably involves the inflammatory, vascular, and neurotropic effect of the coronavirus. While short‐, mid‐and long‐term consequences remain unclear, patients with neurocognitive sequelae reminiscent of other cognitive disorders, including AD have been reported. The aim of this study is to investigate if there is an increased risk for long‐term cognitive dysfunction/impairment, biochemical and structural brain changes after a severe COVID‐19. Method: This is a prospective cohort study of 80 patients surviving intensive‐care for COVID‐19 at Karolinska University Hospital, Stockholm, Sweden. They will be examined at 3, 6 and 12 months after hospital discharge using neurological and neuropsychological (NP) tests combined with novel quantitative brain MRI and serial blood sampling to described relevant blood‐borne molecular patterns. This presentation focuses on NP testing, cognitive, mental, and neurological aspects at 3 months follow‐up. Cognitive testing and questionnaires (NP) include Rey Auditory Verbal Learning Test Rey Complex Figure test, Verbal Fluency Test, Category flow, Trail Making Test Symbol Digit Modalities Test, Mental Fatigue Scale, the Hospital Anxiety and Depression Scale, RAND‐36, AD8 Dementia Screening Interview and Subjective cognitive decline questions. A detailed neurological examination (neurologist), including Expanded Disability Status Scale, an adapted version of the Unified Parkinson's Disease Rating Scale for extrapyramidal dysfunction, and a brief smell test. Results: At present, 28 participants have completed the 3‐months follow‐up visit, including neuropsychological and neurological examinations. Mean age (SD) at baseline was 57.8 (11.1) years, and 68% were men. Several patients expressed cognitive and/or mental concerns and fatigue. The neuropsychological and neurological examinations have so far revealed varying and mixed patterns. Brain MRI revealed mainly microvascular pathology. Detailed analyses, including blood biomarkers for neuronal injury and astrocytic activation, based on the 3‐months examination will be presented. Conclusions: Repeated examinations will allow further analyses on longer term impact on cognition and underlying mechanisms. This may identify patients at risk and possible ways to mitigate cognitive complications, which is of great importance to reduce the pandemic's negative effects and socioeconomic burden.